Effect of sulfite on the sensorial quality of minimally processed jackfruit (Artocarpus heterophyllus Lam) - Gepes, Reah Paguntalan (2004.)
Vegetable vendors in Iloilo City Terminal Market (ICTM) practice the use of sodium metabisulfite on minimally processed jackfruit in order to minimize browning and intensify consumer acceptability.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Sulfite; Jackfruit; Artocarpus heterophyllus lam